Score of Toxic Epidermal Necrosis Predicts the Outcomes of Pediatric Epidermal Necrolysis. Issue 4 (16th May 2017) - Sorrell, Jennifer; Anthony, Lisa; Rademaker, Alfred; Belknap, Steven M.; Callahan, Shields; West, Dennis P.; Paller, Amy S.
Abstract: Background/Objectives: Epidermal necrolysis (Stevens–Johnson syndrome and toxic epidermal necrolysis) includes immune‐mediated, life‐threatening inflammatory blistering disorders that can affect children. The Score of Toxic Epidermal Necrosis (SCORTEN) tool has accurately predicted the outcome of these disorders in adults but has not been tested in children. Methods: We performed a retrospective chart review to compare the accuracy of the adult SCORTEN tool with that of two modifications tailored to children in predicting disease outcome. Results: The longer the patient's median length of hospital stay was, the higher the adult and two proposed pediatric SCORTENs were. In addition, all patients who died had SCORTENs greater than 4. Conclusion: The pediatric‐modified tools were not superior to the adult SCORTEN, which accurately predicted outcome.